Brain atlas of the African mole‐rat Fukomys anselli. Issue 11 (22nd February 2019) - Dollas, Alexa; Oelschläger, Helmut H. A.; Begall, Sabine; Burda, Hynek; Malkemper, Erich Pascal
Abstract: African mole‐rats are subterranean rodents that spend their whole life in underground burrow systems. They show a range of morphological and physiological adaptations to their ecotope, for instance severely reduced eyes and specialized somatosensory, olfactory, and auditory systems. These adaptations are also reflected in the accessory sensory pathways in the brain that process the input coming from the sensory organs. So far, a brain atlas was available only for the naked mole‐rat ( Heterocephalus glaber ). The Ansell's mole‐rat ( Fukomys anselli ) has been the subject of many investigations in various disciplines (ethology, sensory physiology, and anatomy) including magnetic orientation. It is therefore surprising that an atlas of the brain of this species was not available so far. Here, we present a comprehensive atlas of the Ansell's mole‐rat brain based on Nissl and Klüver‐Barrera stained sections. We identify and label 375 brain regions and discuss selected differences from the brain of the closely related naked mole‐rat as well as from epigeic mammals (rat), with a particular focus on the auditory brainstem. This atlas can serve as a reference for future neuroanatomical investigations of subterranean mammals. Abstract : The Ansell's mole‐rat is a eusocial subterranean rodent from Zambia (photo by Sarah Maria Wilms). It displays diverse sensory adaptations to the underground environment, which are reflected in the central nervous system. Here, we present an anatomical atlas of the Ansell's mole‐rat brain identifying 375 regions on 56 plates.